2022
DOI: 10.1002/adma.202204976
|View full text |Cite
|
Sign up to set email alerts
|

Spleen‐Targeted Glabridin‐Loaded Nanoparticles Regulate Polarization of Monocyte/Macrophage (Mo/Mφ) for the Treatment of Cerebral Ischemia‐Reperfusion Injury

Abstract: ischemia can cause an ischemic core and salvageable surrounding tissue (termed as penumbra). The penumbra has been regarded as a pharmacological target for ischemic stroke treatment. [2] Restoring cerebral blood flow is currently the most effective approach for reducing the number of damaged neuron in the ischemic penumbra. [3] Although intravenous thrombolysis can effectively restore blood supply in the penumbra, its use is limited by a short time window during which it can be safely and effectively performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 42 publications
(31 reference statements)
0
12
0
Order By: Relevance
“…The modified neurological severity score (mNSS) has been employed for assessing neurological deficits in animal models of traumatic brain injury . A higher mNSS score signifies a more compromised neurofunctional status in mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The modified neurological severity score (mNSS) has been employed for assessing neurological deficits in animal models of traumatic brain injury . A higher mNSS score signifies a more compromised neurofunctional status in mice.…”
Section: Resultsmentioning
confidence: 99%
“…The modified neurological severity score (mNSS) has been employed for assessing neurological deficits in animal models of traumatic brain injury. 37 A higher mNSS score signifies a more compromised neurofunctional status in mice. Our findings (Figure 8A,B) demonstrated that the ICH group exhibited a pronounced increase in mNSS scores on days 1, 3, and 7 post-ICH, compared with the sham group, indicating neurofunctional deterioration.…”
Section: Evaluation Of Neurological Function In Micementioning
confidence: 99%
“…[ 13 ] Researchers have recently found that glabridin could inhibit the pro‐inflammatory M1 polarization and enhance the anti‐inflammatory M2 polarization of monocyte and macrophage (Mo/Mϕ). [ 14 ] Modulating the phenotype of Mo/Mϕ has been adopted as a promising strategy to accelerate wound healing. [ 15 ] The pharmaceutical functions of glabridin also include antioxidants, [ 16 ] and antibacterial activities, which positively impact wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…[13] This specifically suggests that the monocyte/macrophage lineage is part of the pathogenesis of pristane-induced DPH, and thus may be a potential therapeutic target. [12,14] This study aimed to investigate the efficacy of MSCs and MSC-EVs in DPH mouse models and to elucidate the mechanism of MSCs/MSC-EVs on mononuclear/phagocyte differentiation in the injured lung.…”
Section: Introductionmentioning
confidence: 99%